Notes of Some Indonesian Literary Critics - Donny Syofyan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The tension between the individual standpoint and the communal perspective often lends colour to the works of literary critics of Indonesian literature. The use of communal perspectives in critiques and personal ideologies of critics are openly declared in their works. The communal perspective outweighs any liberal or conservative beliefs as the aim of most literary critics is to advocate for the development of the society. As such, literary critics either focus on reconciling progressive ideas with cultural values or criticise liberal themes since they prefer to maintain social ideals. Although Indonesia has some progressive values that are followed in the society, the traditional values that existed before colonialism are considered as superior and more beneficial to the society.Ketegangan antara sudut pandang individu dan perspektif komunal sering kali memberikan warna pada karya-karya kritikus sastra sastra Indonesia. Penggunaan perspektif komunal dalam kritik dan ideologi pribadi kritik dinyatakan secara terbuka dalam karya mereka. Perspektif komunal lebih banyak daripada kepercayaan liberal atau konservatif karena tujuan dari para kritikus sastra adalah untuk memajukan pengembangan masyarakat. Dengan demikian, para kritikus sastra fokus pada rekonsiliasi ide -ide progresif dengan nilai -nilai budaya atau mengkritik tema-tema liberal karena mereka lebih suka mempertahankan cita -cita sosial. Meskipun Indonesia memiliki beberapa nilai progresif yang diikuti dalam masyarakat, nilai -nilai tradisional yang ada sebelum kolonialisme dianggap lebih unggul dan lebih bermanfaat bagi masyarakat.